2016
DOI: 10.1007/s00394-016-1331-9
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of caffeine-containing energy drinks on physical performance: a systematic review and meta-analysis

Abstract: ED ingestion improved performance in muscle strength and endurance, endurance exercise tests, jumping and sport-specific actions. However, the improvement in performance was associated with taurine dosage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
84
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(97 citation statements)
references
References 49 publications
4
84
0
9
Order By: Relevance
“…The current meta-analysis was based on studies providing isolated doses of taurine and not those co-ingesting with other supplements. Interestingly, our analysis confirms the suggestions of a previous meta-analysis [8], where taurine was assumed to explain the ergogenic effects of energy drinks. Only one study from the current analysis was shared between the two meta-analyses, owing to the number of experimental groups included by Kammerer et al [18].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The current meta-analysis was based on studies providing isolated doses of taurine and not those co-ingesting with other supplements. Interestingly, our analysis confirms the suggestions of a previous meta-analysis [8], where taurine was assumed to explain the ergogenic effects of energy drinks. Only one study from the current analysis was shared between the two meta-analyses, owing to the number of experimental groups included by Kammerer et al [18].…”
Section: Discussionsupporting
confidence: 90%
“…The lack of historical interest in isolated taurine supplementation and human performance is somewhat surprising, given its inclusion in popular energy drinks, and its purported contribution to their ergogenic effects. Indeed, a recent meta-analysis demonstrated that the dosage of taurine, as opposed to caffeine, when co-ingested in energy drinks explained their effects on different types of exercise performance [8]. However, the authors did not include investigations using isolated taurine supplementation, focussing on co-ingested energy drinks alone.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous narrative reviews on caffeine's effects on endurance performance have been published [3,4,[8][9][10][11][12], however, the available meta-analyses' are either old or do not accurately assess the effects of caffeine on endurance performance [1,5,13,14]. A meta-analysis by Doherty and Smith [5] was published in 2004, the same year that caffeine was removed from the WADA banned list and a large number of studies have since investigated the effects of caffeine as an ergogenic aid.…”
Section: Introductionmentioning
confidence: 99%
“…However, the authors only included studies which had closed-end performance tests which lasted 45 s-8 min. The meta-analysis by Souza et al [13] only included studies that used energy drinks, many of which contain other potentially ergogenic substances such as taurine which might influence the outcome. This means that the effects of caffeine could not be isolated and the effect of the energy drinks on performance could not be directly attributed to caffeine.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews and analyses, which synthesize the outputs of many studies into a pooled estimate of outcome are at the top of the evidence hierarchy. Indeed, such information is available on products such as caffeine (Burke, 2008;Conger et al, 2011;Glaister & Gissaine, 2017), including its specific delivery in energy drinks (Souza et al, 2017), bicarbonate (Carr et al, 2011b), creatine (Branch, 2003;Mujika & Padilla, 1997), b-alanine (Hobson et al, 2012;Saunders et al, 2016), nitrate/beetroot juice (Hoon et al, 2013;McMahon et al, 2017), antioxidant supplements (Braakhuis & Hopkins, 2015), N-acetylcysteine (Rhodes & Braakhuis, 2017), and polyphenols (Somerville et al, 2017). Other meta-analyses target specific uses of sports products, such as, in the case of sports drinks and gels, carbohydrate intake during endurance sport (Stellingwerff & Cox, 2014).…”
mentioning
confidence: 99%